"IAmSizeSexy": A health communication body image study. Issue 6 (24th August 2022) - Thompson, Carly; Paprzycki, Peter; Demers, April; Tagoe, Ishmael; Kruse-Diehr, Aaron J.; Glassman, Tavis
Abstract: Objective: The aim of this study was to formatively evaluate a health communication campaign on body image targeting undergraduate female students. Participants: A total of 331 students at a large public Midwestern university participated in the study. Methods: Researchers used central intercept procedures to recruit students from residence halls. After viewing the campaign materials, students completed an online survey assessing their message endorsement and level of eating disorder symptomology and provided open-ended comments. Results: Students appreciated the message and thought it was effective, though students with greater body image concerns were less receptive to the message. Thematic analysis indicated students perceive body image to be a relevant issue, yet they want the university to provide more attention to, and information on, the topic. Conclusions: Overall, students understood the message and found it helpful. Nevertheless, students with body image issues responded less favorably, warranting the need for secondary and tertiary prevention.